Pengaruh Pemahaman Kode Etik Profesi Akuntansi dan Kecerdasan Manusia Terhadap Perilaku Etis Mahasiswa Akuntansi Kalbis - Gabriella Felicia Korompis; Budi Kurniawan (UNIVERSITAS KALBIS, 2022)
This study aims to examine and obtain empirical evidence of the effect of understanding the code of ethics of the accounting profession, and human intelligence on the ethical behavior of Kalbis Institute students. The population in this study were active students in the Kalbis Institute morning class class 2017 – 2020. The number of samples in this study was 125 students and by proportional random sampling the amount of research data obtained was 95 students. The data analysis method used is simple and multiple linear regression. The test results show a significance value of 0.000 < 0.05, so it can be ascertained that understanding the code of ethics of the accounting profession, and human intelligence affect the ethical behavior of Kalbis Institute students.